Insulin-Like Growth Factors in Development, Cancers and Aging - Werner, Haim (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Cells on "Insulin-Like Growth Factors in Development, Cancers and Aging" provides a collection of modern articles dealing with the role of insulin-like growth factors (IGF1) in cancer biology, aging and development. Featured articles explore basic and clinical aspects of the IGF1 system, including post-genomic analyses as well as novel approaches to target the IGF1 receptor (IGF1R) in oncology. The present Special Issue highlights some of the most important topics in the broad area of IGF research, including the role of IGF1 in aging and longevity, attempts to target the IGF1 axis in oncology, the role of IGF-binding proteins, structural aspects of IGF-II, etc. We trust that this assembly of articles will be of great help to students, basic researchers and practitioners.